Occupational Exposure to Lead Decreases Macular, Choroidal, and Retinal Nerve Fiber Layer Thickness in Industrial Battery Workers*. (August 2014) - Ekinci, Metin; Ceylan, Erdinç; Çağatay, H. Hüseyin; Keleş, Sadullah; Altınkaynak, Hasan; Kartal, Baki; Koban, Yaran; Hüseyinoğlu, Nergiz
Abstract Purpose: To evaluate the toxic effects of chronic lead (Pb) exposure on retinal nerve fiber layer thickness (RNFLT), macular thickness (MT) and choroidal thickness (CT) in battery industry workers. Materials and Methods: Male factory workers (n = 50) and healthy non-employees (n = 20) participated in the study. Group 1 (n = 22) comprised lead workers; Group 2 (n = 16), box makers; Group 3 (n = 12), assistant personnel; and Group 4 (n = 20), healthy non-employees. All participants were given Best-Corrected Visual Acuity (BCVA) tests, full ophthalmologic examinations, and Spectral Domain Optical Coherence Tomography (SD-OCT) of the optic nerve head, RNFL, macula, and choroid. Blood lead levels (BLL) in venous blood samples were determined. The duration of exposure to lead varied, and is expressed in months. Results: Average (mean ± SD) ages of participants were 27.55 ± 4.00, 28.69 ± 3.48, 32.00 ± 3.38, and 29.85 ± 5.48 yrs (Groups 1–4, respectively). BLL were 46.2 ± 2.32, 29.31 ± 3.30, 16.9 ± 1.9, and 2.85 ± 0.98 µg/dL (Groups 1–4, respectively). Durations of exposure to lead were 43.86 ± 10.81, 42.81 ± 4.86, and 49.42 ± 6.14 mo (Groups 1–3, respectively). OCT averages for RNFL were 101.68 ± 5.32, 119.50 ± 13.47, 127.67 ± 8.92, and 130.9 ± 6.63 μm (Groups 1–4, respectively). Although RNFLTs of Group 1 were significantly less than those of for Groups 2–4, and, RNFLTs of Groups 2 and 3 were significantly less than that of Group 4, there were no significant differences between Group 2 and 3. MTs were 94.50 ± 6.78, 105.63 ± 5.43, 111.50 ± 6.74 and 147.95 ± 6.67 μm, (Groups 1–4, respectively). CTs were 176.41 ± 15.39, 222.19 ± 17.79, 239.17 ± 15.64, and 251.50 ± 10.98 μm (Groups 1–4, respectively). Both MTs and CTs displayed significant differences among the four groups. Conclusions: Ocular changes in individuals who are chronically exposed to lead include decrease in RNFT, MT, and CT, and thus these parameters should be evaluated during ophthalmologic examination of individuals working in lead-based industries.